What Makes It Difficult for Free Trade Agreements to Apply In Indonesia - Shinta Ayu Sri Yunindhar; Siti Nuryanah (Jurnal Akuntansi dan Perpajakan, 2023)
This study aims to analyze the reasons why free-trade agreements are difficult to apply in Indonesia by analyzing tax disputes over certificates of origin (CoO). The fulfillment of the CoO requirements determines whether import duty reduction in the free trade agreement can be granted. This research is a case study of customs audits and re-examinations using content analysis and semi-structured interviews. Primary data will be obtained through semi-structured interviews conducted with the Auditor’s Representative, Audit Quality Supervisor, and Audit Results Evaluator. The secondary data used were from 150 tax court decisions. The results showed that there are still evidentiary problems, unclear procedures, differences in understanding of the rules, and rationalization from importers on the use of CoO. This condition is supported by differences in judges' beliefs in deciding disputes. This research contributes to the consideration of auditors and importers in handling CoO examinations, regulators in making and updating policies, and judges in deciding disputes.